Equalities in freefall? Ontological insecurity and the long‐term impact of COVID‐19 in the academy. (13th August 2020) - Wright, Katharine A.M.; Haastrup, Toni; Guerrina, Roberta
Abstract : This intervention focuses on the impact of the global crisis resulting from the COVID‐19 pandemic on existing racialized and gendered inequalities within the academy and in particular our discipline of Politics and International Relations. We argue that responses to recent crises within the academy have exacerbated ontological insecurity among minoritized groups, including women. When coupled with increased caring responsibilities, the current crises call into question who can be creative and innovative, necessary conditions for knowledge production. While university managers seek to reassure university staff of the temporary nature of COVID‐19 interventions, we argue that the possibilities for progressive leaps at a later state of institutional regeneration is unlikely when efforts to address structural inequalities are sidelined and crisis responses are undertaken which run counter to such work.